Evaluation of interprofessional training to strengthen communication and coordination among providers working with expectant mothers and infants affected by substance use. (January 2022) - West, Allison; Schultz, David; Schacht, Rebecca L.; Barnet, Beth; DiClemente, Carlo; Leonardi LaCasse, Mary
Highlights: Interprofessional training may improve services for infants affected by substance use. Child welfare, early intervention, and home visiting staff are key service providers. Training showed preliminary effects on provider competencies for collaboration. Providers described the training as acceptable and useful. Abstract: Providers across disciplines need knowledge, attitudes, confidence and resources to communicate and collaborate effectively when working with families with infants affected by substance use. This pre-post study assessed the acceptability, perceived utility, and preliminary outcomes of a hybrid online and in-person interprofessional training program for 104 providers working in child welfare, early intervention, and maternal and early childhood home visiting programs. Participants completed a baseline self-report pretest survey, a hybrid online and in-person training program, and a posttest survey. Quantitative data were analyzed using paired t tests; qualitative data from open-ended questions were analyzed using thematic coding. Quantitative data indicated improvements in knowledge and confidence across all provider types, and improvements in home visitor and early intervention providers' perceptions of having the resources to collaborate with child welfare. Overall, the training was described as acceptable and useful. Findings provide initial support for interprofessional training to improve provider competence and collaborative capacity for working with families and infants affected by substance use.